Acanthosis nigricans in a patient with metastatic insulinoma post peptide receptor radionuclide therapy. (1st June 2022) - Yun, Jenny S W; McCormack, Chris; Goh, Michelle; Chiang, Cherie
Abstract : Summary: Acanthosis nigricans (AN) is a common dermatosis associated with hyperinsulinemia and insulin resistance. However, AN has been rarely reported in patients with insulinoma, a state of persistent hyperinsulinemia. We present a case of metastatic insulinoma, in whom AN manifested after the first cycle of peptide receptor radionuclide therapy (PRRT). A 40-year-old man was diagnosed with metastatic insulinoma after 5 months of symptomatic hypoglycemia. Within 1 month post PRRT, the patient became euglycemic but developed a pigmented, pruritic rash which was confirmed on biopsy as AN. We discuss the rare manifestation of AN in subjects with insulinoma, the role of insulin in the pathogenesis of AN, malignant AN in non-insulin-secreting malignancies and association with other insulin-resistant endocrinopathies such as acromegaly. Learning points: Acanthosis nigricans (AN) is a common dermatosis which is typically asymptomatic and associated with the hyperinsulinemic state. Malignant AN can rapidly spread, cause pruritus and affect mucosa and the oral cavity. AN is extremely rare in patients with insulinoma despite marked hyperinsulinemia. Peptide receptor radionuclide therapy might have triggered TGF-α secretion in this subject which led to malignant AN. Rapid spread or unusual distribution of pruritic AN warrants further investigation to exclude underlying malignancy.